Makna Simbolik Abut Nuif Pasu dalam Tradisi Kematian Suku Tmaisan dan Implikasinya bagi Pengembangan Iman Umat Paroki Maubesi - Bele, Flora M.; Ukat, Kristophorus; Mau, Lusius Tae (JURNAL PROPHETA, 2023)
The research entitled The Symbolic Meaning of "Abut Nuif Pasu" in the Death Tradition of the Tmaisan Tribe and Its Implications for the Development of the Faith of Maubesi Parish People has the aim of finding out the symbolic meaning contained in the Death Tradition of the Tmaisan Tribe and its implications for the development of the faith of Catholics in the Parish of Saint Yohanes Maria Vianney Maubesi. The research method used is qualitative research with 3 data collection techniques, observation, interviews and documentation. The research results show that the attitudes and actions of cultural people will be in line with the religious values ??they adhere to because the positive norms and values ??of cultural practices are carried out in line with the teachings of the people's faith. The most important thing is the implications for the development of the people's faith. The implications of the symbolic meaning of “abut nuif pasu” in the amut tradition are that people believe in the power of God who gives life both in this world and in the afterlife, people establish bonds of love and brotherhood in a community, people firmly believe in God's promise of eternal happiness in life, so they try to to avoid actions that are prohibited by God.